Corporate transparency and reserve management: Evidence from US property-liability insurance companies - Han, Sangyong; Lai, Gene C.; Ho, Chia-Ling (Journal of Banking & Finance, 2018)
Using a sample of US publicly traded property-liability insurers, we examine the effect of corporate transparency on earnings management. We find that a higher level of corporate transparency is associated with more conservative loss-reserves estimation. Our evidence shows that the positive effect of corporate transparency on insurers’ reserves-estimate conservatism is more pronounced for insurers that are smaller and have more diversified lines of business and that certain board characteristics—such as being smaller, meeting more frequently, and having a higher percentage of independent directors—can restrain the inadequate reserves management of less transparent US publicly traded property-liability insurers. We also provide evidence that additional regulatory mandates to seek greater transparency in the Sarbanes-Oxley Act may be redundant, given the existing regulations in the property-liability insurance industry. Finally, we find insurers’ conservative reserve estimates were more pronounced during the 2008–2009 financial crisis.